Analysis and Design of Motorcycle Financing Systems at POS Semesta Finance: Analysis and Design of Motorcycle Financing Systems at POS Semesta Finance - Arie Gunawan (Jurnal Mantik, 2020)
The development of information and technology in Indonesia is currently progressing very rapidly, so that inevitably a company must not be left behind in implementing it. This implementation is in the form of system development from manual to computerized or even computerized systems that are redeveloped into an integrated system. This study aims to analyze and design a motorcycle financing system in accordance with user needs. The old system that is running and used in the SPU (Service Point Unit) is not possible to be applied to POS (Point of Sale). Therefore, the design is done from the beginning by following the existing systems and procedures. The motorcycle financing system being developed is expected to provide an increase compared to using the manual method. Some of the expected improvements include system performance, the information provided, the economic level and the level of control that can be carried out. With this increase, it is hoped that it can also improve the performance of employees who will also improve service to consumers.